Second Five Year Plan Punjab State Review of Progress for 1958-59 - Planning Commission (Planning Commission, 1958)
The Second Five-Year Plan has been formulated to develop the country's economic and social structure on democratic lines. Such a democratically framed national Development Programme naturally derives its strength from regional plans whose success during a particular period generally got reflected in their contribution to the general health of the economy. The contribution of the Punjab Second Plan to its economy has been quite substantial as revealed by the following resume of progress for the year 1958-59. The Slate Second Five-Year Plan provides a total outlay of Rs 162.68 crores which corresponds to the Plan ceiling of Rs 4,800 crores for the country as a whole.
Planning Department Punjab State